Investigation and analysis of thermo-mechanical degradation of fingers in a photovoltaic module under thermal cyclic stress conditions. (1st November 2018) - Kumar, Sagarika; Gupta, Rajesh
Highlights: 3-D FEM developed to simulate thermo-mechanical behavior of fingers in PV modules. Finger-solder interface found to be vulnerable to thermal cyclic conditions. Trade-off between power loss and thermo-mechanical stability with finger spacing. Solder thickness identified as key parameter for finger-solder joint reliability. Acceleration factor estimated between Indian site weather cycle and thermal cycle. Abstract: The reliability of current carrying fingers in a photovoltaic (PV) cell is essential to the overall performance of a PV module. The close proximity of the fingers to the solder layer makes it compelling to investigate its reliability under the premise of solder joint degradation, which is susceptible to high temperature transient variations. For the investigation of this particular aspect of finger reliability, a 3-D finite element model (FEM) of a PV module has been simulated under accelerated thermal cycle (TC) and outdoor weather temperature cycles. The FEM has been optimised to reduce computational complexity for accommodation of the small size of fingers in comparison to other components. Experimental TC test has also been performed on PV module batches to support the simulated findings by characterisation of observed finger breakages using illuminated current-voltage (I-V) and electroluminescence (EL) imaging technique. The finger-solder interface was identified to be vulnerable under prevailing thermal loading conditions, from both the simulated and experimental findings. To illustrate a larger spectrum of finger reliability, the influence of variable geometrical design parameters of finger and solder layer have been investigated for its dependence on electrical power loss and thermo-mechanical damage accumulation. It was demonstrated that solder thickness and finger spacing are key to the performance of fingers in a PV module. Under the outdoor weather temperature cycle the finger-solder interface was found to be more vulnerable to damage accumulation during the sunshine hours on a hot day as compared to a cold day. Further, an acceleration factor was estimated to establish a quantitative comparison between the outdoor weather temperature cycle and accelerated TC. This paper highlights the different aspects of thermo-mechanical degradation of fingers in PV modules under transient thermal conditions and is instrumental for optimization of variable design and packaging parameters for its enhanced reliability.